Analisis Pengaruh Store Atmosphere terhadap Purchase Decision dengan Customer Attitude dan Percieved Value sebagai Variabel Mediasi - Sianturi, Intan Angelie (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the influence of store atmosphere on purchase decisions with customer attitude and perceived value as mediating variables in the context of KFC fast-food restaurants. Using a quantitative approach and structural equation modeling (SEM) analysis, the study reveals that store atmosphere has a significant positive effect on purchase decisions. The findings also indicate that customer attitude and perceived value play a crucial role in mediating this relationship. A comfortable and appealing store atmosphere enhances customers' positive attitudes toward the brand store atmospheres, thereby strengthening the relationship between customers and the brand.